PERAN PUSTAKAWAN DI ERA GLOBALISASI - Azzahra, Imanisa Nila (Perpustakaan Universitas Muhammadiyah Ponorogo, 2024)
Abstract. This article discusses the crucial role of librarians in facing the challenges of globalization and digitalization. As the frontline in library management, librarians are responsible for ensuring that the public and library users can effectively access information and knowledge. Globalization has brought significant changes in society's preferences, with an increasing reliance on digital technology over conventional methods. Therefore, librarians are required to have strong technological skills, manage digital collections such as e-books, e-journals, online databases, and audiovisual materials, and provide fast, innovative services that meet the needs of the digital natives generation.Moreover, librarians must adapt to the rapid revolution of information, provide integrated services, and add value to the information provided. Libraries now serve not only as repositories of physical collections but also as digital service centers that facilitate access to information in various formats. Thus, the role of librarians extends beyond collection management, positioning them as active agents of change who are innovative and responsive to the needs of modern society.This article emphasizes that the success of librarians in facing the challenges of globalization relies heavily on their ability to transform and enhance digital-based services, meeting the public's expectations for quick, easy, and relevantÂ information.